Mortality statistics in a tertiary care teaching hospital in Bagalkot, Karnataka in the year 2022 - Shankar, Gowri; Sidenur, Bhagyalaxmi; Kalburgi, Eshwar B. (International Journal Of Community Medicine And Public Health, 2023)
Background: Mortality statistics is important for epidemiological purposes to find any unusual rise in deaths for investigation of the causes so as to take public health action at an early stage. Cause of death statistics from hospitals are routinely amalgamated along with mortality statistics from other sources to constitute essential statistics on the health of a population. This study was done to understand the mortality pattern in a tertiary care teaching hospital and to undertake preventive action as much as possible. Methods: A retrospective hospital based study was done with all the medical records of patients who died in Hangal Sri Kumareshwar hospital and medical research centre in the year 2022, attached to S. N. Medical College, Bagalkot, Karnataka. After IRB, the medical records were analyzed to study the pattern of disease causing deaths which were classified under ICD 10th revision. Age, sex, month of admission, place of residence and underlying cause of death was used for analysis using chi square test and percentages. Results: Out of 501 deaths, 316 (63.07%) were male and 185 (36.93%) were female. Majority of the deaths 152 (30.34%) occurred between the ages of 41 to 60 years. Non communicable diseases contributed to 71.05% of deaths and communicable diseases to 28.95% of deaths. Conclusions: Continuation of the maternal and child health program and effective implementation of the National health programs to overcome non communicable diseases can reduce avoidable premature mortality in the population.